2010
DOI: 10.5194/acpd-10-14897-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Composition and temporal behavior of ambient ions in the boreal forest

Abstract: A recently developed atmospheric pressure interface mass spectrometer (APi-TOF) measured the negative and positive ambient ion composition at a boreal forest site. As observed in previous studies, the negative ions were dominated by strong organic and inorganic acids (e.g. malonic, nitric and sulfuric acid), whereas the positive ions consisted of strong bases (e.g. alkyl pyridines and quinolines). Several new ions and clusters of ions were identified based on their exact masses, made possible by the high resol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 59 publications
0
39
0
Order By: Relevance
“…The experimental measurements of ambient ions in boreal forests by Ehn et al (2010) included both positively and negatively charged ions. The molecules that were subjected to study were selected based on the molecular formula of the (uncharged) compounds identified in the measured positive mass spectra.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental measurements of ambient ions in boreal forests by Ehn et al (2010) included both positively and negatively charged ions. The molecules that were subjected to study were selected based on the molecular formula of the (uncharged) compounds identified in the measured positive mass spectra.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
“…2. Largest calculated proton affinities (green squares) for each compound and the mean of 30 min average concentrations over the measurement period (black circles; Ehn et al, 2010). The value of the x axis is merely an index referring to the legend.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The uncertainties in the fitted model parameters (m L2 = [k wall , γ SOA , Y] T ) were evaluated using the statistics of nonlinear regression. 21 We obtain 95% confidence limits on the model parameters by: 21 σ = 1.96 diag(Cov(m L2 )) 1/2 [6] We estimate the covariance matrix (inverse Hessian) for the fitted model parameters as: 21 Cov(m L2 ) ≈ s 2 (J(m L2 ) T J(m L2 )) −1 [7] S8 where Cov(m L2 ) is the covariance matrix for a the model results linearized about m L2 , s is the measurement standard deviation, and J(m L2 ) is the Jacobian matrix (dr/dm) of the residual vector r, calculated about the least-squares solution m L2 using finite differences.…”
Section: S7mentioning
confidence: 99%
“…5 The FIXCIT inlet was used in the calibrations to maintain the same f inlet values. Malonic acid (C 3 H 4 O 4 ) was the most sensitive organic compound tested and was used as the primary LVOC calibrant since it is thought to cluster at rates close to the collision limit 6 . The calibration factor calculated from Equation 3 using the malonic acid k ion measurements and FIXCIT f inlet of 7% is C = 7.9 x 10 10 molec.…”
Section: No 3 --Cims Quantificationmentioning
confidence: 99%